VALUASI EKONOMI KAWASAN KONSERVASI (ILUSTRASI PENDEKATAN BIAYA PERJALANAN) - Muhammad Subardin (Jurnal Ekonomi Pembangunan, 2009)
Travel cost approach is an approach already widely used and easiest to do the valuation of natural resources and environment, particularly for environmental services related to recreational activities.  The relationship between the cost of travel and number of visits is assumed to represent the demand for recreation.  This travel cost method to estimate the demand curve and calculate the consumer surplus to the conservation area. It seems like the demand curve, then the price represents the cost of travel (leisure) and the number of visits represents the quantity (recreation).  Such relations are obtained by developing a simple regression model that shows the influence of travel costs and demographic variables visitor to the number of visits.  Thus, the increase in travel costs (and tariffs) resulted in a decline the visit because it was considered too expensive.  Travel costs increased mainly because of the distance where the greater the distance between the place of residence it will be increasingly less demand for recreational areas. Keywords: travel cost, valuation, demand for recreation, consumer surplus, conservation area